THE POTENTIAL POLLINATORS OF CAESALPINIA CRISTA (LEGUMINOSAE : CAESALPINIOIDAE) - SOUGRAKPAM NELI; JATIN KALITA (The Bioscan, 2013)
Caesalpinia crista is one of the economically important medicinal plants of the family Leguminosae and is considered to be one of the best medicines to cure malaria. It is a large straggling, very thorny shrub with hooks and straight hard yellow prickles with nectaries at its base which attracts a considerable number of nectar feeding insects as it is an insect pollinated plant. The pollination ecology of C. crista was investigated through direct observation and video recording during the flowering period for three consecutive years (2009-2011) at Rani Reserve Forest, Assam, North Eastern India situated at 26º01' N to 26º06' N Latitude and 91º35' E to 91º42' E Longitude. In this present study, 22 species of insects were recorded in association with the plant among which 10 are major pollinators and the remaining 12 are minor pollinators of the plant. Among the 10 pollinator insects, seven potential pollinators was found to be exclusively bee species, Apis cerana, Anthophora semperi, Xylocopa aestuens, Xylocopa latipes, Megachile disjuncta, Megachile latipes and Megachile sp. Future conservation and management of this medicinally important plant species needs to take into account the needs and biology of its potential pollinators.